2021
DOI: 10.3389/fphar.2021.609901
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Antihypertensive Medication Use and Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: Background: The prevalence rate of hypertension and breast cancer increases with advancing age. Renin-angiotensin system inhibitors (RASIs), β-blockers (BBs), calcium channel blockers (CCBs), and diuretics are widely used to treat patients with hypertension. Although, the association between the use of antihypertensive medication and breast cancer has been highly debated, recent evidence supporting this association remains controversial.Objective: To evaluate the association between the use of antihypertensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 82 publications
(95 reference statements)
1
14
2
Order By: Relevance
“…Studies have reported that women who used antihypertensive medications showed an increased improvement in the BC treatment compared to those without prescriptions of antihypertensive drugs. 31 , 34 …”
Section: Hypertension and Breast Cancermentioning
confidence: 99%
“…Studies have reported that women who used antihypertensive medications showed an increased improvement in the BC treatment compared to those without prescriptions of antihypertensive drugs. 31 , 34 …”
Section: Hypertension and Breast Cancermentioning
confidence: 99%
“…For example, health registries and EHR are often very large and matched to contemporary practice, but may have limited value with regards to treatment, comorbidity, cancer subtype, and other adjustment data to extract causality insights (as compared to some trial datasets) (Mack et al, 2018). As such, it would be useful if Xie et al (2021) provides clear information on the data types used in each metastudy and whether results differ according to registry/EHR versus clinical trial data.…”
Section: Type Of Datamentioning
confidence: 99%
“…We note that Cardwell et al (2014) and Cui et al (2019) provide explicit statements on their methodologies to account for immortal time bias (nested case-control and time-dependent approach respectively). We would appreciate it if Xie et al (2021) could provide information on whether each study used methodologies to mitigate immortal time bias, and whether meta-analysis results differed between studies that did and did not account for immortal time bias.…”
Section: Immortal Time Biasmentioning
confidence: 99%
See 2 more Smart Citations